Competitive repopulation of an empty microglial niche yields functionally distinct subsets of microglia-like cells. Issue 1 (December 2018) - Lund, Harald; Pieber, Melanie; Parsa, Roham; Han, Jinming; Grommisch, David; Ewing, Ewoud; Kular, Lara; Needhamsen, Maria; Espinosa, Alexander; Nilsson, Emma; Överby, Anna; Butovsky, Oleg; et al.
Abstract Circulating monocytes can compete for virtually any tissue macrophage niche and become long-lived replacements that are phenotypically indistinguishable from their embryonic counterparts. As the factors regulating this process are incompletely understood, we studied niche competition in the brain by depleting microglia with >95% efficiency usingCx3cr1 CreER/+ R26 DTA/+ mice and monitored long-term repopulation. Here we show that the microglial niche is repopulated within weeks by a combination of local proliferation of CX3CR1+ F4/80low Clec12a– microglia and infiltration of CX3CR1+ F4/80hi Clec12a+ macrophages that arise directly from Ly6Chi monocytes. This colonization is independent of blood brain barrier breakdown, paralleled by vascular activation, and regulated by type I interferon. Ly6Chi monocytes upregulate microglia gene expression and adopt microglia DNA methylation signatures, but retain a distinct gene signature from proliferating microglia, displaying altered surface marker expression, phagocytic capacity and cytokine production. Our results demonstrate that monocytes are imprinted by the CNS microenvironment but remain transcriptionally, epigenetically and functionally distinct. Brain microglial cells can be replenished by blood-derived monocytes, but many aspects of this repopulation remain unclear. Here the authors show that the brain microglial niche can be replaced both by proliferating, residential microglia as well as differentiated Ly6Chi monocytes, with the latter having overlapping but distinct characteristics.